Analysis of redox status and HDL subclasses in patients with lymphoma and the associations with FDG-PET/CT findings - Mirjanic-Azaric, Bosa; Stankovic, Sinisa; Nezic, Lana; Radic Savic, Zana; Malcic- Zanic, Dragana; Skrbic, Ranko; Kotur-Stevuljevic, Jelena; Bogavac-Stanojevic, Natasa (Frontiers in Oncology, 2023)
Newer research points to alterations in the plasma redox status and the HDL subclass distributions in cancer. We aimed to assess the redox status and the HDL subclass distributions, lipids, and inflammatory markers in lymphoma patients in order to determine whether they were correlated with changes in FDG-PET/CT scans. At the beginning of this study, redox status, HDL subclasses, lipids, and inflammation biomarkers were determined in 58 patients with lymphoma (Hodgkin lymphoma, n=11 and non-Hodgkin lymphoma, n=47), and these same measurements were reassessed during their ensuing treatment (in 25 patients). Initially, the total oxidation status (TOS), the prooxidant–antioxidant balance (PAB), the OS index (OSI), the total protein sulfhydryl groups (SH-groups), and the advanced oxidation protein products (AOPP) were significantly higher in lymphoma patients as compared to healthy subjects, but the total antioxidant status (TAS) was significantly reduced. The PAB had a strong correlation with the CRP and interleukin- 6 (rho=0.726, p<0.001; rho=0.386, p=0.003). The correlations between these parameters and the maximum standardized uptake values (SUVmax) were: PAB, rho=0.335 and p=0.010; SH-groups, rho=0.265 and p=0.044; CRP, rho=0.391 and p=0.002; HDL3b, rho=0.283 and p=0.031; HDL2b, rho= -0.294 and p=0.025; and HDL size, rho= -0.295 and p=0.024. The reductions in SUVmax between two follow-up points were associated with increases in the OSI, TOS, and SH-groups, as well as a reduction in the PAB and TAS. In conclusion, the redox parameters in patients with lymphoma were consistent with FDG-PET/CT findings. Targeting the redox status parameters and the HDL subclasses could be potential strategies in the molecular fight against lymphoma.